Crises and critical junctures in authoritarian regimes: addressing uprisings' temporalities and discontinuities - Frédéric Volpi; Johannes Gerschewski (Third World Quarterly, 2020)
In this article, we aim at sharpening common understandings of the notion of political crisis to better explain the trajectories of authoritarian transformations during popular uprisings. We make three major claims. First, we propose a definition of crisis as brief moments of institutional fluidity and openness in which a process can take different directions. We delineate the crisis concept from the concept of critical junctures and outline how our approach contributes to the methodological debate on `near misses'. Second, we indicate how the de-institutionalisation processes leading up to a crisis are to be analytically distinguished from within-crisis moments. We argue in favour of a discontinuity approach that takes into account the different temporalities of gradual lead-up processes and rapid within-crisis dynamics. Finally, we illustrate our theoretical and analytical reasoning with concrete cases from the authoritarian crises of the Arab uprisings, whilst suggesting that our argument can travel to other areas of research in which crisis narratives have gained prominence.
Keywords: 330; crisis; critical juncture; de-institutionalisation; situational logics; near misses; authoritarianism; Arab uprisings